SPE International Conference on Health, Safety, and Environment 2014
DOI: 10.2118/168321-ms
|View full text |Cite
|
Sign up to set email alerts
|

HPHT Cement Sheath Integrity Evaluation Method for Unconventional Wells

Abstract: Chances of cement sheath failure increase considerably when the application involves deepwater, high pressure high temperature (HPHT) conditions. Such failures may occur as a result of temperature and pressure-induced stresses created by well events such as hydraulic fracturing, cyclic steam injection, steam assisted gravity drainage (SAGD), production, completion, or other remedial treatments. Thermal and stress cycles could impose the risk of losing zonal isolation and lead to delay in hydrocarbon production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 12 publications
0
15
0
2
Order By: Relevance
“…The imposed stresses therefore have the potential to induce cracks in the cement column and create microannuli [2]. Weak bonding can cause failure at cement-casing or cement-formation interfaces [3,4]. These defects in the cement sheath could adversely affect their sealing capacity to provide zonal isolation, resulting in gas/liquid migration through the flow paths created by cement failure and even serious leak or blowout accidents.…”
mentioning
confidence: 99%
“…The imposed stresses therefore have the potential to induce cracks in the cement column and create microannuli [2]. Weak bonding can cause failure at cement-casing or cement-formation interfaces [3,4]. These defects in the cement sheath could adversely affect their sealing capacity to provide zonal isolation, resulting in gas/liquid migration through the flow paths created by cement failure and even serious leak or blowout accidents.…”
mentioning
confidence: 99%
“…Properties impacting zonal isolation in this period include fluid loss (filtration), free fluid development (bleeding), gel strength development, chemical shrinkage, and permeability (Nelson and Guillot, 2006). The required short-term properties are summarized below (Nelson and Guillot, 2006;Ravi et al, 2002;Shadravan et al, 2014;Williams et al, 2011) :…”
Section: Factors Influencing Zonal Isolationmentioning
confidence: 99%
“…As described in the previous section, cement sheaths typically fail because of volumetric instability and imposed tensile stresses beyond the tensile strength of the cement sheath. (Shadravan et al, 2014;Williams et al, 2011) Pressure increase is more damaging because the fluid injection lasts from minutes to hours (Thiercelin et al, 1998) Several have suggested requirements to tensile strength, Young's modulus, and other mechanical properties of the cement sheath to provide a long-term zonal isolation through long-term stress evaluation (Bois et al, 2011;Bois et al, 2012;Roy-Delage et al, 2000;Saint-Marc et al, 2008;Stiles and Hollies, 2002). Thiercelin et al (1998) analyzed different stress conditions in oil wells which were applicable for most types of loading.…”
Section: Requirements To Cement Systems To Provide Long-term Zonal Ismentioning
confidence: 99%
See 1 more Smart Citation
“…To address potential issues and help operators make well-informed decisions regarding the long-term integrity of oil and gas wells, many companies, both in the service and operation sectors, have applied to some extent a more comprehensive approach when designing OWCs, taking advantage of the evolution of OWCs, both from the chemical (new systems) and engineering (new characterization tools) perspectives, to create an optimal sealant to help ensure integrity for the life of the well (Fig. In support of this statement, many studies report successful use of such techniques in yielding optimum long-term wellbore integrity in actual or simulated downhole environments (Krusche et al 2006;Shadravan et al 2014Shadravan et al , 2015aShadravan et al , 2015bGarnier et al 2007;De Andrade et al 2015;Godoy et al 2015;McDaniel et al 2014b;Griffith et al 2004;Jain et al 2014;Wang and Dahi Taleghani 2014b;Ramos et al 2009). Multiple datasets indicate significant variations in wellbore integrity (2.6 to 75%) over different time periods (Davies et al 2014).…”
Section: Impact Of Owc Evolution On Wellbore Construction Economics Amentioning
confidence: 99%